An Agent-Based Model of Heterogeneous Demand - Müller, Matthias (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2017)
Matthias Müller makes a case for the particular role of the demand side in research on innovation. Based on a complex agent-based simulation model, he analyzes the versatile mutual relationships between consumers and producers within the innovation process. Instead of oversimplifying the demand side, the book aims to apply important aspects which too often are only applied to the supply side, e.g., the heterogeneity and bounded rationality of economic actors embedded in networks. The results offer a new perspective on the innovation process, proving that the demand side and consumers are important drivers of innovation, which must be included in future research for a full picture. Contents The Role of Consumers in Innovation Economics Evolutionary Economics The New Agent-Based Paradigm in Economics An ABM of Heterogeneous Consumers and Demand Consumer Networks Bounded Morality of Consumers Target Groups Researchers and students in the fields of innovation economics, evolutionary economics, complexity science, and computer simulation Policy making, public administration, and innovation management The Author Matthias Müller conducted his doctoral research at the University of Hohenheim, Germany. He currently works as a postdoctoral researcher in the field of innovation economics.
Keywords: Social sciences.; elektronické knihy; electronic books